IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA DALAM PEMBELAJARAN PAI : Tinjauan Analisis Pada Pendidikan Dasar Menengah dan Tinggi - Sitti Chadidjah; Agus Kusnayat; Uus Ruswandi; Bambang Syamsul Arifin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
The implementation of moderation values of religion is very important to discuss, considering that several schools have entered into radical and extreme views, and anarchist demonstrations have recently been carried out by SMA/SMK students. Concern is a problem that must be resolved, otherwise it will cause instability in the nation. This nation will continue to fight, fight, quarrel over things that are not principles. The implementation of The implementation of moderation values ​​in SD, SMP, SMA, and tertiary institutions has the same conceptual foundation, namely wasthiyah, which consists of tasamuh, tawazun and i'tidal. Currently, moderation values ​​are emphasized in the subjects of Islamic religious education at all levels of education. Although currently the implementation of the value of moderation is still hidden in the curriculum, in attitude, schools have made tasamuh, tawazun and i'tidal attitudes mandatory in elementary, junior high and high school environments. Meanwhile, in higher education, this habituation is not obvious. This study uses a qualitative approach, with the research library method, by carrying out a careful reading of various literature, sorting out information that is directly related, identified, understood, then analyzed Key word; implementation, value, moderate